2023
DOI: 10.1038/s41598-023-31305-4
|View full text |Cite|
|
Sign up to set email alerts
|

Optimization of Parylene C and Parylene N thin films for use in cellular co-culture and tissue barrier models

Abstract: Parylene has been used widely used as a coating on medical devices. It has also been used to fabricate thin films and porous membranes upon which to grow cells. Porous membranes are integral components of in vitro tissue barrier and co-culture models, and their interaction with cells and tissues affects the performance and physiological relevance of these model systems. Parylene C and Parylene N are two biocompatible Parylene variants with potential for use in these models, but their effect on cellular behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…A neuron-like cell line, PC-12, was also cultured on UV-treated parylene-C and parylene-N films, which induced simultaneous proliferation and differentiation of PC-12 cells with neurite outgrowth . Recently, the influence of parylene films for the other kinds of cells was reported for HUVEC cells, NTera2.D1 astrocyte cell, cancer cells. These results indicate that the chemical environment supplied by the functionalized parylene films can influence the proliferation and differentiation of the cultured cells. In this study, antibody-producing hybridoma cells were cultured on modified parylene films to produce a monoclonal antibody against the well-known fungal toxin, ochratoxin-A (OTA) .…”
Section: Introductionmentioning
confidence: 97%
“…A neuron-like cell line, PC-12, was also cultured on UV-treated parylene-C and parylene-N films, which induced simultaneous proliferation and differentiation of PC-12 cells with neurite outgrowth . Recently, the influence of parylene films for the other kinds of cells was reported for HUVEC cells, NTera2.D1 astrocyte cell, cancer cells. These results indicate that the chemical environment supplied by the functionalized parylene films can influence the proliferation and differentiation of the cultured cells. In this study, antibody-producing hybridoma cells were cultured on modified parylene films to produce a monoclonal antibody against the well-known fungal toxin, ochratoxin-A (OTA) .…”
Section: Introductionmentioning
confidence: 97%
“…Among these choices, parylene-C a chlorinated variant among the various parylene class of polymers is an excellent choice for ultraflexible applications as it is highly versatile and offers several advantages such as high mechanical flexibility, conformability, moisture and chemical resistivity, transparency, dielectric property, light weight, and excellent adhesion to substrates. [61][62][63][64] In this work, we have fabricated AgNWs-PEDOT:PSS based ultraflexible TCE spincoated on 5 μm parylene-C substrate and have investigated its optoelectrical, mechanical, and material characteristics. Finally, using this electrode we have fabricated an ultraflexible OPD, and its performance is evaluated and compared with standard ITO-based OPD.…”
Section: Introductionmentioning
confidence: 99%
“…Among these choices, parylene‐C a chlorinated variant among the various parylene class of polymers is an excellent choice for ultraflexible applications as it is highly versatile and offers several advantages such as high mechanical flexibility, conformability, moisture and chemical resistivity, transparency, dielectric property, light weight, and excellent adhesion to substrates. [ 61–64 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few reports have shown that coating resin-3D-printed materials with parylene C increased their compatibility with hardy cell lines in direct or indirect contact with the materials. For cells cultured directly on the 3D-printed substrate, parylene coating has been used successfully with endothelial cells and the epithelial cell line MDCK . Parylene was also effective in an indirect context, i.e., for the culture of cell lines including keratinocyte HaCaTs and primary neuronal cells on PDMS chips molded from parylene-coated 3D-printed master molds .…”
mentioning
confidence: 99%